THE INFLUENCE OF EFFECTIVE COMMUNICATION AND THE UTILIZATION OF INFORMATION TECHNOLOGY ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE IN MEDAN MAYOR OFFICE - Siti Kemala Sari Tambunan; Yeni Absah; Elisabet Siahaan (CV. Radja Publika, 2023)
Human resources are an important aspect of an organization because the productivity achieved by employees can have a direct impact on the organization. Factors that can improve employee performance are effective communication and the use of information technology. In addition, job satisfaction is also a causal aspect that improves employee performance. The purpose of this research is to analyze the effect of effective communication and the use of information technology on employee performance through job satisfaction. The population and sample in this study were 131 employees of the Kantor Walikota Medan. Data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. The results of the study show that effective communication directly has a positive and significant effect on job satisfaction, the use of information technology has a positive and significant effect on job satisfaction, effective communication has a positive and significant effect on employee performance, the use of information technology has a positive and significant effect on employee performance, and satisfaction work has a positive and significant effect on employee performance. Indirectly, effective communication has a positive and significant effect on employee performance through job satisfaction and the use of information technology has a positive and significant effect on employee performance through job satisfaction.